RESEARCH COMPETITIVE MARKETING STRATEGY OF HUAWEI MOBILE PHONE - Zhixin Li; Ratih Hurriyati; Puspo Dewi Dirgantari (Universitas Pendidikan Indonesia, 2021)
In an era of rapid growth in user demand for smartphones, there are many well-known mobile phone brands, such as Apple, Huawei, Samsung, Xiaomi, OPPO and VIVO in the smartphone market. Competition in the mobile phone market is fierce. In addition, In recent years, Huawei has been subject to technical blockades and trade restrictions from Western countries such as the United States. The situation of Huawei mobile phone is extremely difficult, but Huawei still achieved sales revenue of RMB 454 billion in the first half of 2020, a year-on-year increase of 13.1%, and a net profit margin of 9.2%. The reason why Huawei mobile phones can achieve such impressive sales results is largely due to Huawei's unique marketing strategy. This article uses the SWOT analysis method to specifically analyze the strength, weakness, opportunities and threat faced by Huawei's mobile phone business marketing, and uses the 4P principles of product, price, channel, and promotion to analyze its current development stage, and then use the theory of Michael Porter’s generic competitive strategies analyses and chooses the competition strategy, and then draw conclusions from Huawei’s experience and problems, and provide suggestion for the development of Huawei and other companies